Rúbrica basada en competencias de aprendizaje en un curso CS1 para evaluar actividades de programación CSCL - Hidalgo-Suarez, Carlos-Giovanny; Bucheli-Guerrero, Víctor-Andrés; Ordoñez-Erazo, Hugo-Armando (Revista Científica, 2023)
Programming courses (CS1) have the highest academic mortality rate, this is reflected in the low grades of the students, which indicates that the students do not reach the academic competencies. In this sense, looking for new ways to improve the learning of the students of the CS1 course, this article proposes an analytical rubric based on academic competencies for collaborative programming activities supported by an automatic source code evaluation tool that allows to improve the qualifications and reach the competencies proposed in the course. A rubric was designed with 16 evaluation criteria that were divided into three activities which were presented by an experimental group (EG) of 18 students and a control group (CG) of 24 students. In the GE, a collaboration between students was used, while in the CG, students work individually. After finishing the activities, using an analytical rubric, the deliveries of each student were evaluated to identify if they achieved the learning results expected by the course. The results show that the use of collaboration achieves that students manage to win a learning competition in 17 % more than if they do it individually. In addition, other social skills associated with collaboration are highlighted, such as friendship, motivation and group understanding. The development of strategies that allow to evaluate the competences, not only indicate that the student manages to acquire a skill, but also allows the student to identify their shortcomings in the programming tasks.